KEPUTUSAN PEMBELIAN KOPI ARABIKA ROASTED (STUDI KASUS PADA THE HIDDEN SWARGI COFFEE ROASTER) - Najla Alya Sulma; Nuning Setyowati; Indah Nurhidayati; Erlyna Wida Riptanti (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2026)
The coffee beverage market continues to grow and is increasingly in demand by the public, opening up new profitable business opportunities, such as coffee roastery and coffee shop. One of the coffee roastery and coffee shop businesses in Surakarta is The Hidden Swargi Coffee Roastery. The Hidden Swargi Coffee must pay attention to the desires and preferences of its consumers by formulating a good marketing strategy so as to attract consumer interest in making purchasing decisions. This study aims to analyze the effect of price, product quality, business location, service quality, promotion, and product knowledge on purchasing decisions for roasted arabica coffee at The Hidden Swargi Coffee Roastery in Surakarta, and to analyze the effect of price as a mediating factor for product quality on purchasing decisions and service quality on purchasing decisions. This study uses primary data from a survey of 120 roasted arabica coffee consumers at The Hiddden Swargi Coffee Roastery. The data were analyzed using descriptive analysis and SEM-PLS analysis and software SEM-PLS 4.0. The results showed that there are four factors that have a positive and significant effect on purchasing decisions for roasted arabica coffee at The Hidden Swargi Coffee Roastery in Surakarta, including price, product quality, service quality, and business location. This shows that consumers consider the four factors mentioned above. These results underscore the importance of strategic pricing and comprehensive marketing efforts in enhancing consumer purchasing behavior in the specialty coffee sector.